The relationship between gender identity and depressive symptoms in adolescents: a moderated mediation model of self-efficacy and family functioning - Chenyu Hou; Hanchun Yan; Zhibiao Xiang; Chenyang Leng; Haojuan Tao; Zhening Liu; Hui Lei (BMC Public Health, 2025)
Abstract Background Gender identity is associated with adolescent depression, but the relationship remains unclear. To further clarify the relationship between gender identity and mental health, this study targets adolescents with significant fluctuations in gender identity, constructs a moderated mediation effect model, examines the relationship between gender identity and depression, and explores the mediating role of self-efficacy and the moderating role of family functioning, to provide scientific references for proposing effective psychological interventions for different gender identity groups. Methods Using whole group convenience sampling method, 2341 students from a school in Changsha, Hunan Province, were selected for the survey, and the Patient Health Questionnaire-9 items, the Family Care Index Scale, the General Self-Efficacy Scale-Schwarzer, and gender identity-related questions were used for the assessment of mental health. Results The prevalence of depression was 40.5% among transgender adolescents, which was significantly higher than that of cisgender adolescents (15.6%). At the same time, gender identity, self-efficacy, family functioning, and depression constituted a moderated mediation model, with family functioning moderating the posterior path of this mediation process. Specifically, self-efficacy was progressively less predictive of depression as family functioning increased. Conclusion Transgender adolescents showed significantly poorer mental health than cisgender adolescents. There was a partial mediating effect of self-efficacy between gender identity and adolescent depression, with family functioning moderating the latter half of this mediation effect. This study advances our understanding of the relationship between depression and self-efficacy or family functioning in adolescents of different gender identities.